Keteladanan Kepemimpinan Nehemia Yang Setia Bagi Hamba Tuhan Di Era 4.0 - Sumampouw, Denny (JURNAL ILUMINASI, 2023)
Nehemiah is a classic example of a leader who led by example. He led from the front, and he led from the trenches working right beside his people. Nehemiah was a high official in the Persian King's household. He could have shared his vision and then dispatched others to carry it out.